Biodiesel production from refined used cooking oil using co-metal oxide catalyzed transesterification - Sulaiman, N. F. (Elsevier Ltd., 2020)
The world is challenged with depletion of non-renewable fossil fuel and environmental pollution. Thus, this research was emphasized on converting refined used cooking oil to safer and low toxicity biodiesel by base-catalyzed transesterification reaction. Alumina supported magnesium, calcium, strontium and barium oxide-based catalysts with iron as its dopant were optimized according to various calcination temperatures and iron loadings. The optimum conditions over potential catalyst was achieved with 20 wt% of Fe loading for Fe/Ba/Al2O3 catalyst calcined at 800 °C which gave the maximum biodiesel production of 84.02%. Characterization of catalyst carried out by XRD showed that the 20Fe:80Ba/Al2O3 catalyst calcined at 800 °C had a polycrystalline structure with high BET surface area (133.59 m2/g) while FESEM analysis displayed a morphology of uniform plate-like shape grains with fine particles in the range of 55–60 nm. CO2-TPD results showed that the catalyst exhibited highest basicity of 2.5854 mmol/g, while TGA analysis proved that 800 °C was the optimum calcination temperature. The transesterification process of refined used cooking oil to produce high yield biodiesel was effectively attained using 20Fe:80Ba/Al2O3 catalyst.